A 'data realm' for the Global South? Evidence from Indonesia. - Hicks, Jacqueline (Third World Quarterly, 2021)
This article examines the international and domestic pressures that shape the governance of personal data in the Global South. As developing countries become new terrain for the expansion of US Big Tech and develop their own digital economies, international policy discourses urge the adoption of data governance as self-evidently 'good policy' moving into existing regulatory vacuums. However, like any valuable resource, the competition to govern personal data is subject to existing power relations, political interests, institutional pathways and ideologies. With evidence from Indonesia, this article shows how the governance of personal data in the digital economy is influenced by international and national commercial interests, and instrumentalised by domestic state and political elite. In doing so, it adapts the North American 'information-security complex' for developing countries with their post-colonial economies, self-interested oligarchic elites and hybrid state-commercial data firms. The significance of this approach lies in its realistic understanding of the challenges and opportunities for supporting data governance reform around the world.